Adaptive Communication and Religious Inclusivity in the Electoral Defeat of a Long-Term Incumbent - Ladini, Malisa; Yuwono, Teguh; Yuwanto (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study analyzes the unexpected electoral defeat of a three-term incumbent in the 2024 Provincial Dewan Perwakilan Rakyat Daerah (DPRD) race in Central Java’s Electoral District 4, an area historically characterized by strong Nahdlatul Ulama (NU) socioreligious dominance and long-term Partai Kebangkitan Bangsa (PKB) electoral stability. While existing research on Indonesian local politics underscores incumbency advantage rooted in ritual embeddedness, symbolic authority, and organizational loyalty, such explanations are insufficient to capture the challenger’s unprecedented rise. This article addresses that gap by examining the relational, communicative, and symbolic mechanisms that reshaped voter preferences. Using a qualitative case-study design, the research draws on eighteen semi-structured interviews, participant observation in religious and community events, digital-content analysis, and official data from the General Elections Commission (Komisi Pemilihan Umum, KPU). The findings reveal that the incumbent experienced a substantive decline in symbolic authority due to reduced ritual visibility and diminishing emotional proximity, corresponding with an 8–12% decrease in vote share across key polling-station clusters. Conversely, the challenger constructed legitimacy through embodied service practices, adaptive political communication tailored to diverse audiences, and hybrid digital–offline visibility that amplified everyday interactions into credible public narratives. The study concludes that voter behavior in NU-based rural constituencies is undergoing a cultural reorientation in which sincerity, accessibility, and continuous moral presence now outweigh structural party advantages. These insights expand theoretical discussions on personalization, symbolic legitimacy, and relational politics in Indonesia’s decentralized electoral landscape, providing a more nuanced understanding of how challengers can penetrate entrenched socioreligious strongholds.